Pengembangan Media Hiro Card Pada Mata Pelajaran Matematika Materi Bilangan Romawi Di Kelas IV SD Negeri Sempu 2 Kota Serang: Penelitian dan Pengembangan Pada Siswa Kelas IV SDN Sempu 2 Kota Serang - Siahaan, Fenny Aprianty Siahaan; Michel, Joseph (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2023)
This study aims to: 1) determine the process of developing Hiro Card learning media in mathematics, 2) determine the feasibility of Hiro card learning media in mathematics. This research uses Research and Development (R&D) research using a 4D development model with stages, namely define, design, development, desiminate. This learning media goes through the stages of media validation test, material validation test, and product testing. The subjects of this research are the fourth grade students of SD Negeri Sempu 2 Serang City as many as 25 students. Based on the results of the study, the average validation of media experts was 90 with the